A study on thrombocytopenia in pregnancy and feto-maternal outcome conducted at tertiary care center Rajkot, Gujarat - Prajapati, Shetal; Kumar P. S., Nandan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Thrombocytopenia is second only to anemia as the most common hematological abnormality encountered in pregnancy. Better antenatal care has led to increased detection. Once diagnosed, it is Important to further evaluate and to determine the cause to optimize management. The objectives were to study feto-maternal outcome in patient of thrombocytopenia in terms of maternal and neonatal complications and to study the causes of thrombocytopenia in pregnancy. Methods: The present study was a hospital-based study carried out from June 2021 to June 2022 at the department of obstetrics and gynecology, PDU medical college, Rajkot, Gujarat. During this period 100 patients in the third trimester of pregnancy with thrombocytopenia were selected randomly. Results: In this study 41% cases were mild thrombocytopenia, 39% with moderate and 20% were severe cases. 50% cases were gestational thrombocytopenia, 31% were cases associated with hypertensive disorders of pregnancy, 8% cases were associated with abruption, 13% cases were associated with IUFD, 2% cases were idiopathic thrombocytopenic purpura (ITP), 8% cases were associated with viral (dengue) and bacterial (malaria) infection, 1% cases were associated with SLE, 1% cases was thrombotic thrombocytopenic purpura (TTP). Maternal complications were encountered in form of DIC in 13% cases, jaundice in 7% of cases, 2% cases were complicated by PPH, 4% cases were complicated by acute kidney injury, 2% cases were associated with sickle cell crisis and 4% cases were maternal mortality. 12% were stillbirth and 5% cases had neonatal mortality. Conclusions: Thrombocytopenia in pregnancy induced hypertension carries a risk for both the mother and her fetus. Thrombocytopenia in pregnancy if timely diagnosed do not cause any mortality, however management of these patients require a multidisciplinary approach and close collaboration between obstetrician, physician, and neonatologist.